Sumac silver novel biodegradable nano composite for bio-medical application: antibacterial activity - Ghorbani, Parisa; Soltani, Mozhgan; Homayouni-Tabrizi, Masoud; Namvar, Farideh; Azizi, Susan; Mohamad, Rosfarizan; Moghaddam, Amin Boroumand (MDPI, 2015)
The development of reliable and ecofriendly approaches for the production of nanomaterials is a significant aspect of nanotechnology nowadays. One of the most important methods, which shows enormous potential, is based on the green synthesis of nanoparticles using plant extract. In this paper, we aimed to develop a rapid, environmentally friendly process for the synthesis silver nanoparticles using aqueous extract of sumac. The bioactive compounds of sumac extract seem to play a role in the synthesis and capping of silver nanoparticles. Structural, morphological and optical properties of the nanoparticles were characterized using FTIR, XRD, FESEM and UV-Vis spectroscopy. The formation of Ag-NP was immediate within 10 min and confirmed with an absorbance band centered at 438 nm. The mean particle size for the green synthesized silver nanoparticles is 19.81 ± 3.67 nm and is fairly stable with a zeta potential value of −32.9 mV. The bio-formed Ag-NPs were effective against E. coli with a maximum inhibition zone of 14.3 ± 0.32 mm.